Combined magnetic resonance elastography and collagen molecular magnetic resonance imaging accurately stage liver fibrosis in a rat model. Issue 3 (31st December 2016) - Zhu, Bo; Wei, Lan; Rotile, Nicholas; Day, Helen; Rietz, Tyson; Farrar, Christian T.; Lauwers, Gregory Y.; Tanabe, Kenneth K.; Rosen, Bruce; Fuchs, Bryan C.; Caravan, Peter
Abstract : Hepatic fibrosis is associated with an overproduction of matrix proteins and a pathological increase of liver stiffness. Noninvasive magnetic resonance (MR) quantification of matrix can be assessed with a collagen‐binding molecular MR probe and stiffness by MR elastography, complementary techniques. This study used both imaging techniques to more accurately stage hepatic fibrosis in a rat model. Thirty rats with varying levels of diethylnitrosamine‐induced liver fibrosis were imaged before and 45 minutes after injection of collagen‐specific probe EP‐3533. MR elastography was performed in the same imaging session. Changes in liver relaxation rate post–EP‐3533 and liver stiffness were compared to the collagen proportional area determined by histology and to Ishak scoring using receiver operating characteristic analysis. Collagen imaging was most sensitive to early fibrosis, while elastography was more sensitive to advanced fibrosis. This complementary feature enabled the formulation of a composite model using multivariate analysis of variance. This model incorporated the discriminating advantages of both MR techniques, resulting in more accurate staging throughout fibrotic progression. Conclusion : Collagen molecular MR imaging is complementary to MR elastography, and combining the two techniques in a single exam leads to increased diagnostic accuracy for all stages of fibrosis. (Hepatology 2017;65:1015‐1025)